2023
DOI: 10.3390/vaccines11010136
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practice and Barriers Associated with Influenza Vaccination among Health Care Professionals Working at Tertiary Care Hospitals in Lahore, Pakistan: A Multicenter Analytical Cross-Sectional Study

Abstract: Health Care Professionals (HCPs), including doctors, nurses, pharmacists, and paramedics, are a high-risk group for influenza infection due to their continuous exposure to patients having a known or unknown history of influenza-like illnesses. Influenza vaccination is the most effective method of primary prevention. This study was conducted to assess knowledge, attitude, practice, and barriers associated with influenza vaccination among HCPs at tertiary care hospitals in Lahore, Pakistan. A multicenter analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Further HCPs also understand their role in disease transmission and that vaccination helps prevent infection from spreading to others 19 . Similarly, the "lack of time" was also reported in other studies, and it was also shown that some interventions 20 might increase vaccination rates 21,22 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Further HCPs also understand their role in disease transmission and that vaccination helps prevent infection from spreading to others 19 . Similarly, the "lack of time" was also reported in other studies, and it was also shown that some interventions 20 might increase vaccination rates 21,22 .…”
Section: Discussionsupporting
confidence: 68%
“…Several factors may be related to influenza vaccination, and identifying these can support the development of policies and strategies that expand vaccination coverage 8 . In Pakistan, where the influenza vaccine is recommended for all health workers, scientific production to identify vaccination-related factors in this group priority is still scarce 9 . Several factors may be related to influenza vaccination, and identifying these can support the development of policies and strategies that expand vaccination coverage.…”
Section: Introductionmentioning
confidence: 99%
“…These coverage estimates are higher than previous surveys from Pakistan, which report around 8.8–20.1% of the healthcare workers to be vaccinated and are comparable with other WHO Eastern Mediterranean Region countries. 13 , 16-18 The HCWs in our study had a low level of awareness, as only 25% of them ever made a laboratory-confirmed diagnosis of influenza in their practice and 39% of the HCWs did not perceive themselves to be susceptible to severe disease. Previously, Ali et al reported that 60% of the HCWs believed asymptomatic hospital workers cannot transmit the virus and the vaccine contains a live virus which may cause influenza.…”
Section: Discussionmentioning
confidence: 70%
“…Inferential statistical (chi-squared test) analysis was performed to assess the correlation between the demographic variables and KAP questions. The overall percent score cutoff was computed using the modified Bloom's cutoff point criteria, which had already been used in previous studies ( 24 , 25 ). We chose nine questions for the knowledge part, with each accurate response (yes:1) receiving one point and the incorrect response (no:0) receiving zero points.…”
Section: Methodsmentioning
confidence: 99%
“…The vaccinators were defined as having “good knowledge” if their score was above 75% (ranging from 77.7% to 100% with 7–8 points), “moderate knowledge” if their score ranged from 55% to 74% (5–6 points), and “poor knowledge” if their score was < 55% (< 5 points). The total practice score was categorized as “good practice” if it ranged from 75% to 100% (9–12 points) or “poor practice” if it was < 75% (8 points) ( 24 , 25 ). Logistic regression analysis was used to identify the differences in sociodemographic characteristics between training and non-training variables.…”
Section: Methodsmentioning
confidence: 99%